Spina Bifida and Rehabilitation - Ozaras, Nihal (My University, 2015)
Spina bifida (SB) is the incomplete closure of the posterior elements of the vertebrae due to a developmental disorder. Among the causes of childhood disability, SB is the second most common cause after cerebral palsy. Generally, secondary motor neuron findings are seen below the lesion. The ambulation grade and the orthoses used by patients vary according to the level of the lesion. SB patients experience various complications throughout their lives. The purpose of SB rehabilitation is to prevent these complications and to keep the patient-s functional status at the best possible level. Therefore, a rehabilitation program, starting at infancy and continuing during the lifetime, should be family centered and should be conducted with a multidisciplinary team.